1993
DOI: 10.2165/00003088-199324020-00002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Antiviral Nucleoside Analogues

Abstract: The recent development of nucleoside analogues with antiviral activity has expanded the small but useful armamentarium for the treatment of certain viral diseases such as the human immunodeficiency virus, cytomegalovirus and others. Their intracellular site of action and need for sequential phosphorylation require that traditional pharmacokinetic parameters be used in conjunction with an understanding of intracellular metabolism when designing dosage regimens. This review summarises the available pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(41 citation statements)
references
References 129 publications
2
38
0
1
Order By: Relevance
“…Although little is known about this molecule's pharmacokinetics and toxicity in humans, other molecules of this class (e.g. NSC404241) are well tolerated in humans and are known to cross the blood-brain barrier (31,36), an important prerequisite for treating stage 2 HAT. Besides NSC404241, the molecule NSC63984 has also been shown to cross the blood-brain barrier (32), suggesting that this class of molecules may be explored for the develop- ment of drugs against stage 2 HAT.…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about this molecule's pharmacokinetics and toxicity in humans, other molecules of this class (e.g. NSC404241) are well tolerated in humans and are known to cross the blood-brain barrier (31,36), an important prerequisite for treating stage 2 HAT. Besides NSC404241, the molecule NSC63984 has also been shown to cross the blood-brain barrier (32), suggesting that this class of molecules may be explored for the develop- ment of drugs against stage 2 HAT.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the pharmacokinetic data for IAA with existing GDEPT prodrugs shows that IAA has a considerably shorter half-life (GCV, 2-3 h; 27 5-FC, 3-4 h; 28 CB1954, 1.4-2 h 29 ). This will require the activation of IAA in a more rapid manner than existing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Ganciclovir (GCV), a 2Ј-deoxyguanosine analog, was the first Food and Drug Administration approved drug available in the United States with significant activity against HCMV. It was shown to be 26 times more potent than acyclovir against HCMV in vitro ( Morse et al, 1993). Previous studies reported excellent in vitro activity of GCV against human herpes virus type 6, human herpes simplex viruses types 1 and 2, varicella-zoster virus, and Epstein-Barr virus (Smee et al, 1983;Andrei et al, 1991;Shigeta et al, 1991;Snoeck et al, 1991;Konno et al, 1993).…”
mentioning
confidence: 99%